Profitabilitas Skala: Analisis Komparatif Kinerja Keuangan Usaha Kost - Iman Putra Jaya Ndraha; Krisnawati Setyaningrum Nugraheni (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The boarding house business is a rapidly growing residential rental property sector but has received minimal research from its financial management aspect. This study analyzes the financial performance of three boarding house business models in the Bawen-Ambarawa area using descriptive analysis and financial ratio calculations (NPM, OER, ROI). Data were collected through observation, interviews, and documentation of monthly financial reports for three months. The analysis shows a